The use of bisphosphonates in the management of bone involvement from solid tumours and haematological malignancies – a European survey. (12th April 2016) - Lebret, T.; Casas, A.; Cavo, M.; Woll, P.J.; Deleplace, C.; Kennedy, C.; Schoen, P.; Jackisch, C.
Abstract : Bone metastases in patients with solid tumours (ST) and bone lesions in patients with haematological malignancies (HM) are common. Associated skeletal‐related events (SREs) cause severe pain, reduced quality of life and place a burden on health care resources. Bone‐targeted agents can reduce the risk of SREs. We evaluated the management of bone metastasis/lesions in five European countries (France, Germany, Italy, Spain and the UK) by an observational chart audit. In total, 881 physicians completed brief questionnaires on 17 193 patients during the observation period, and detailed questionnaires for a further 9303 individuals. Patient cases were weighted according to the probability of inclusion. Although a large proportion of patients with bone metastases/lesions were receiving bisphosphonates, many had their treatment stopped (ST, 19%; HM, 36%) or will never be treated (ST, 18%; HM, 13%). The results were generally similar across the countries, although German patients were more likely to have asymptomatic bone lesions detected during routine imaging. In conclusion, many patients who could benefit from bone‐targeted agents do not receive bisphosphonates and many have their treatment stopped when they could benefit from continued treatment. Developing treatment guidelines, educating physicians and increasing the availability of new agents could benefit patients and reduce costs.